Research on the healthy life expectancy of older adult individuals in China based on intrinsic capacity health standards and social stratification analysis - Liu, Mengya; Zhang, Meng; Zhou, Jinglei; Song, Nannan; Zhang, Li (Frontiers in Public Health, 2024)
Background Based on the health standard of intrinsic capacity, this paper conducts an empirical study on the healthy life expectancy of older adult individuals aged 60 and older in China and analyzes the health inequities associated with different social characteristics to provide a reference for improving care for the older adult in China. Methods Data from the China Health and Retirement Longitudinal Study from 2011 to 2015 were used to evaluate the intrinsic capacity level of older adult individuals, and the multistate life table method was used to measure the healthy life expectancy of older adult individuals in China with the help of IMaCH software. Based on the theory of social stratification, the health inequality between older adult individuals in different social classes was analyzed in three dimensions: residence, income and education level. Results The calculation results show that the average life expectancy of the older adult in China at age 60 is 21.07 years, the healthy life expectancy is 16.89 years, and the healthy life expectancy accounts for 80.2% of the average life expectancy. The healthy life expectancy of older adult individuals with different social characteristics in China shows significant differences, and the healthy life expectancy of older adult individuals who are male, live in urban environments, have high levels of education and have middle- to high-income levels is significantly better than that of older adult individuals who are female, live in rural areas, have low levels of education and income. Conclusion Healthy life expectancy measured by intrinsic capacity as the health standard has a certain reference value, which reflects the overall health level of older adult individuals in China and expands the transformation and multidimensional understanding of the healthy thinking of older adult individuals in China. The analysis by social stratification reflects the large health inequities that exist in the older adult population in China.